2010
DOI: 10.1158/1055-9965.epi-10-0243
|View full text |Cite
|
Sign up to set email alerts
|

Nonmelanoma Skin Cancer and the Risk of Second Primary Cancers: a Systematic Review

Abstract: Background: Based on empirical evidence, a personal history of nonmelanoma skin cancer (NMSC) has been hypothesized to be a risk factor for other cancers. Others hypothesize that NMSC may be a marker of high cutaneous vitamin D synthesis and therefore inversely associated with risk of other malignancies. To reconcile these divergent views, we carried out a systematic review to determine the association between NMSC and subsequent risk of other cancers.Methods: Bibliographic databases were searched through Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
87
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 45 publications
10
87
1
4
Order By: Relevance
“…reports, except that the risk estimate tended to be lower in the present study (multivariable-adjusted HR ¼ 2.22) than those reported in previous case-control or registry-based studies (HR/ meta-analysis relative risk > 2.70) (6)(7)(8) and in a prospective study with a total of 19 174 individuals and a 16-year follow-up (multivariable-adjusted relative risk ¼ 7.94) (9). The modest associations reported in our study may be partly explained by the adjustment for a number of potential risk factors.…”
Section: Articlecontrasting
confidence: 89%
See 1 more Smart Citation
“…reports, except that the risk estimate tended to be lower in the present study (multivariable-adjusted HR ¼ 2.22) than those reported in previous case-control or registry-based studies (HR/ meta-analysis relative risk > 2.70) (6)(7)(8) and in a prospective study with a total of 19 174 individuals and a 16-year follow-up (multivariable-adjusted relative risk ¼ 7.94) (9). The modest associations reported in our study may be partly explained by the adjustment for a number of potential risk factors.…”
Section: Articlecontrasting
confidence: 89%
“…Methods: We followed 91 846 women in the Nurses' Health Study (NHS; 1984-2010, 114 918 women in the NHSII , and 48 946 men in the Health Professionals Follow-up Study (1986-2010 for diagnoses of KC and melanoma biennially. Cox proportional hazards models were used to compute hazard ratios (HRs) and 95% confidence intervals (CIs) of melanoma associated with history of KC, basal cell carcinoma (BCC), and squamous cell carcinoma (SCC).…”
mentioning
confidence: 99%
“…116 More recently Wehner et al found in their prospective cohort that the 5-year probability of another NMSC after diagnosis of a first was 40.7%, and 82% after more than 1. 117 At 10 years, the chances increased to 59.6% of another NMSC after the first and 91.2% after diagnosis of a nonfirst NMSC.…”
Section: Follow-up and Reducing Risk For Future Skin Cancersmentioning
confidence: 97%
“…[116][117][118][119]123,[125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141] …”
Section: Follow-up and Reducing Risk For Future Skin Cancersunclassified
“…The two key known mechanisms of cutaneous carcinogenesis are UV-induced genetic damage and suppression of skin immune tumor surveillance responses (3). UV exposure is considered to account for an increased risk of subsequent NMSC and melanoma in individuals after a first NMSC (4,5).…”
Section: Introductionmentioning
confidence: 99%